La Rhétorique d'Aristote et les études de droit - Le May, Denis (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1988)
This paper attempts to link Aristotle's Rhetoric and the contemporary study of law. In the first part, Aristotle's Rhetoric is presented generally, with emphasis on its objective, scope and methodology ; the field of study also delimited in relation to logic and dialectics. The second part shows the relevancy and interest of the Rhetoric in three fundamental areas of the study of law, namely, openness of mind towards psychological and social aspects of law, learning the art of argumentation and methodology of intellectual work in general. The conclusion invites the reintroduction of the teaching of rhetoric in the curriculum.